Experiments in the EpiDerm 3D Skin In Vitro Model and Minipigs In Vivo Indicate Comparatively Lower In Vivo Skin Sensitivity of Topically Applied Aneugenic Compounds. (22nd January 2021) - Schuler, Maik; Tomlinson, Lindsay; Homiski, Michael; Cheung, Jennifer; Zhan, Yutian; Coffing, Stephanie; Engel, Maria; Rubitski, Elizabeth; Seitis, Gary; Hales, Katherine; Robertson, Andrew; Vispute, Saurabh; et al.
Abstract: Risk management of in vitro aneugens for topically applied compounds is not clearly defined because there is no validated methodology to accurately measure compound concentration in proliferating stratum basale keratinocytes of the skin. Here, we experimentally tested several known aneugens in the EpiDerm reconstructed human skin in vitro micronucleus assay and compared the results to flow cytometric mechanistic biomarkers ( phospho -H3; MPM2, DNA content). We then evaluated similar biomarkers (Ki-67, nuclear area) using immunohistochemistry in skin sections of minipigs following topical exposure the potent aneugens, colchicine, and hesperadin. Data from the EpiDerm model showed positive micronucleus responses for all aneugens tested following topical or direct media dosing with similar sensitivity when adjusted for applied dose. Quantitative benchmark dose-response analysis exhibited increases in the mitotic index biomarkers phospho -H3 and MPM2 for tubulin binders and polyploidy for aurora kinase inhibitors are at least as sensitive as the micronucleus endpoint. By comparison, the aneugens tested did not induce histopathological changes, increases in Ki-67 immunolabeling or nuclear area in skin sections from the in vivo minipig study at doses in significant excess of those eliciting a response in vitro . Results indicate the EpiDerm in vitro micronucleus assay is suitable for the hazard identification of aneugens. The lack of response in the minipig studies indicates that the barrier function of the minipig skin, which is comparable to human skin, protects from the effects of aneugens in vivo . These results provide a basis for conducting additional studies in the future to further refine this understanding.